Penggunaan Aplikasi Mobile Eating Learning “M-EL” bagi Ibu sebagai Pola Asuh Autoritatif Upaya Kemandirian saat Anak Makan (Journal of Telenursing (JOTING), 2024)
This study aims to determine the use of M-El Mobile Eating Learning applications for mothers as parenting authorities of independence when children eat. This research method uses a combination of methods, namely the System Development Life Cycle (SLDC) Waterfall to design software in M-El mobile applications. The results showed that the use of M-El applications was effective in parenting (p-value 0.001) independence (p-value 0.031) and the BMW method (p-value 0.001), where the value of p-value